Transforming Islamic Education through Merdeka Curriculum in Pesantren - Wasehudin, Wasehudin; Rohman, Abdul; Nizarudin Wajdi, Muh Barid; Marwan, Marwan (Jurnal Pendidikan Islam, 2023)
The evolution of Islamic education in Indonesia marks a significant shift, with the proactive introduction of the Merdeka Curriculum fostering innovation. This curriculum grants educational institutions the power to tailor their programs to local needs, embodying a dynamic response to contemporary demands. Investigating its implementation at Pesantren Darul Qolam in Banten, this qualitative study involves interviews with Pesantren leaders, teachers, and students, complemented by observational analyses. The findings showcase Pesantren's successful integration of the Merdeka Curriculum, harmonizing it with the national curriculum and designing programs responsive to students' diverse needs. This research advocates for Pesantren institutions to adopt the Merdeka Curriculum, recognizing it as a catalyst for elevating the quality and relevance of Islamic education. Furthermore, it urges a thorough exploration of the curriculum's long-term effects within the Pesantren context and its potential applicability to other Islamic educational institutions. Emphasizing principles of freedom, autonomy in learning, multilingualism, and responsiveness to student needs, the study underscores the crucial role of educational innovation in Pesantren and beyond.